Factors correlated with the postoperative recurrence of chronic subdural hematoma: An umbrella study of systematic reviews and meta-analyses. (January 2022) - Zhu, Fulei; Wang, Haifeng; Li, Wenchen; Han, Shuai; Yuan, Jiangyuan; Zhang, Chunyun; Li, Zean; Fan, Guangyan; Liu, Xuanhui; Nie, Meng; Bie, Li
Summary: Background: Chronic subdural hematoma (CSDH) is a common neurological disease, and the surgical evacuation of subdural collection remains the primary treatment approach for symptomatic patients. Postoperative recurrence is a serious complication, and several factors are correlated with postoperative recurrence. Methods: We searched Embase, Web of Science, PubMed, and Cochrane Library from their establishment to September 2020. Reports on randomized, prospective, retrospective, and overall observational studies on the management of surgical patients with CSDH were searched, and an independent reviewer performed research quality assessment. Factors that affect the postoperative recurrence of CSDH were extracted: social demographics, drugs (as the main or auxiliary treatment), surgical management, imaging, and other risk factors. We evaluated the recurrence rate of each risk factor. A random effect model was used to perform a meta-analysis, and each risk factor affecting the postoperative recurrence of CSDH was then evaluated and graded. Findings: In total, 402 studies were included in this analysis and 32 potential risk factors were evaluated. Among these, 21 were significantly associated with the postoperative recurrence of CSDH. Three risk factors (male, bilateral hematoma, and no drainage) had convincing evidence. The classification of evidence can help clinicians identify significant risk factors for the postoperative recurrence of CSDH. Interpretation: Only few associations were supported by high-quality evidence. Factors with high-quality evidence may be important for treating and preventing CSDH recurrence. Our results can be used as a basis for improving clinical treatment strategies and designing preventive methods. Funding: No funding was received.